2021
DOI: 10.11604/pamj.2021.40.162.29021
|View full text |Cite
|
Sign up to set email alerts
|

Trends and factors associated with repeated adolescent pregnancies in Tanzania from 2004-2016: evidence from Tanzania demographic and health surveys

Abstract: Introduction a repeated pregnancy represents a failure of health and social systems to educate and provide the necessary services and skills to ensure adolescent girls do not experience any further unwanted pregnancies during this young age. We aimed to determine trends and factors associated with repeated adolescent pregnancies in Tanzania 2004-2016. Methods an analytical cross-sectional study was conducted using secondary data from Tanzania demographic and health surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Living with a partner was revealed in our study to contribute to recurrent teenage pregnancies. Ngoda et al [ 27 ] indicated that marriage is a factor that influences recurrent teenage pregnancy because married couples live together, encouraging unprotected sexual intercourse and consequent, recurring pregnancies for the teenager.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Living with a partner was revealed in our study to contribute to recurrent teenage pregnancies. Ngoda et al [ 27 ] indicated that marriage is a factor that influences recurrent teenage pregnancy because married couples live together, encouraging unprotected sexual intercourse and consequent, recurring pregnancies for the teenager.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Inadequate knowledge on family planning was also identified as a contributor to recurrent teenage pregnancies. Albuquerque et al [ 46 ] and Ngoda et al [ 27 ] acknowledged that there is a low prevalence of recurrent pregnancies amongst teenage mothers who use contraceptives, as family planning protects mothers from unplanned pregnancies.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiencing another delivery before the age of 20 years may lead to unfavorable perinatal outcomes in a higher proportion than in the first childbirth. Repeated pregnancy in adolescence is more common in contexts of poverty, low education level, sexual initiation before the age of 15 years, early union, no use of effective contraceptive methods, and previous abortion or dead fetus birth [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…This shows a significant decline from 18.9% in 2015 and 2016 which is significantly lower compared to the national average of 32%. 9 So unmet needs for Family Planning is high among adolescents aged 15 to 19 years in Tanzania and there is poor progress in rates of unmet need for modern contraception use (30% in 2004/05, 25.3% in 2010 and 26.5% in 2015/16 respectively. 8 )…”
Section: Introductionmentioning
confidence: 99%